Can different definitions of date of cancer incidence explain observed international variation in cancer survival? An ICBP SURVMARK-2 study. (August 2020) - Myklebust, Tor Åge; Andersson, Therese; Bardot, Aude; Vernon, Sally; Gavin, Anna; Fitzpatrick, Deirdre; Jerm, Marianne Brenn; Rutherford, Mark; Parkin, D. Maxwell; Sasieni, Peter; Arnold, Melina; Soerjomataram, Isabelle; et al.
Abstract: Background: Differences in registration practices across population-based cancer registries may contribute to international variation in survival estimates. In particular, there are variations in recorded date of incidence (DOI) as cancer registries have access to different sources of information and use different rules to determine an official DOI. This study investigates the impact of different DOI rules on cancer survival estimates. Materials and methods: Detailed data on dates of pathological confirmation and hospital admittance were collected from three registries participating in the ICBP SURVMARK-2 project (England, Northern Ireland and Norway). Multiple dates of incidence were determined for each cancer patient diagnosed during 2010–2014 by applying three sets of rules that prioritize either: a) histological date, b) hospital admittance date or c) the earliest date recorded. For each set of rules and registry, 1- and 5-year net survival were estimated for eight cancer sites (oesophagus, stomach, colon, rectum, liver, pancreas, lung and ovary). Results: The mean difference between different DOIs within a country and cancer site ranged from 0.1–23 days. The variation in 1- and 5-year net survival using different DOIs were generally small for all registries and cancer sites. Only for liver and pancreatic cancer in Norway and ovarian cancer in England, were larger 1-year survival differences, of 2–3 % found. Conclusion: In the ongoing discussion of the comparability of survival estimates across registry populations, the use of different DOI definitions can be considered to have a very limited impact.